Comparative analysis of composition and spatial variations in the foregut microbiota of male and female donkeys - Wang, Yanwei; Li, Xiaotong; Li, Zuowei; Han, Qiaoqiao; Hu, Tong; Zhang, Qiyue; Qu, Honglei; Zhang, Haihua; Qu, Yangyan; Shi, Donghui; Ma, Qiugang; Huang, Shimeng (Frontiers in Microbiology, 2025)
Donkeys, as significant herbivorous mammals, also serve as valuable companion animals. Research on gut microbiota has underscored the essential role of microorganisms in maintaining gut health, supporting nutrient metabolism, and regulating immune function. As the gut microbiota is also shaped by factors such as sex, age, diet, environment and genetics, many studies have on the complexity and diversity of hindgut microbial communities, while few studies have focused on the foregut microbiota of donkeys. To address this gap, we conducted high-throughput sequencing of the highly variable V3-V4 region of the 16S rRNA gene from the donkey small intestine (duodenum, jejunum, and ileum) to characterize and compare microbiota composition and abundance between male and female donkeys. A total of 12 healthy and uniformly conditioned Dezhou donkeys (six males and six females, aged 2–3 years, 250 ± 10 kg in weight) were included in the study. The results showed that albumin (ALB), total cholesterol (TC), and high-density lipoprotein cholesterol (HDL-C) levels were significantly higher (p < 0.05) in the female group compared to the male group. Additionally, α-diversity indices (Ace, Chao, Simpson, and Sobs) were significantly different (p < 0.05) between the groups. The PCoA results indicated significant differences (p < 0.05) between male and female donkeys across all intestinal locations (R2 = 0.2372, p < 0.001). Similarly, the microbial composition of the jejunum (R2 = 0.1875, p = 0.019) and ileum (R2 = 0.1776, p = 0.007) showed significant differences between male and female donkeys. Additionally, Firmicutes, Fusobacteriota, Proteobacteria, and Actinobacteriota were the dominant phyla across all gut regions. In male and female donkeys, key genera included Lactobacillus, Streptococcus, Sarcina, and Escherichia-Shigella. Linear discriminant analysis effect size (LEfSe) analysis revealed gender-specific enrichment, with Clostridium_sensu_stricto_1, Acinetobacter, and NK4A214_group dominant in female duodenum and jejunum, while Streptococcus and Erysipelotrichaceae_UCG-002 were enriched in males. Similarly, female ileum had enriched Amnipila, Terrisporobacter, and Luteimonas, whereas males showed higher levels of Sarcina and Streptococcus. Blautia and Mogibacterium were enriched in female duodenum and jejunum, while Fusobacterium, Actinobacillus, and Moraxella were more abundant in male ileum. These findings characterize the gut microbiota of healthy donkeys and provide novel insights into the differences between male and female donkeys, offering previously unknown information about donkey gut microbiota.